Response of Barley to Different Levels of Water Under Sprinklers in Environment Arid - Ibrahim, Y M; Nadaf, Sakeem K; Nadaf, Saleem K; Al-Lawati, Ali H; Khamisi, S A L (Annals of Arid Zone, 2016)
The rainfed Omani barley 'Duraqui' was studied for its response, with respect to yield and yield contributing characters. to three moisture levels under sprinklers during winter, 1995-96 at Agriculture Research Center (ARC) and Livestock Research Center (LRC), located at Rumais in South Batinah region of Sultanate of Oman. Water levels had a significant effect only for total water applied, while the location effect was significant for plant height, spike weight, grain yield and WUE (grain yield). The interaction effect between water level and location was evident for both grain al}d biological yields. The expressions of all the characters, except total tillers were of higher magnitude in the crop at LRC, as compared to ARC, because of better quality of soil and irrigation water. Although grain and biological yields at LRC increased with increasing levels of water, water use efficiency (WUE) for grain yield was higher for low water level.Â· At ARC. yield differences were non significant and yields were of low magnitude. WUE was significantly higher for low water level. The nature and magnitude of pooled character correlations of high and low water levels were different. There were 28 significant correlations out of 45 character combinations under high water level, while under low water level there were only 16 significant correlations.